(untitled) (Islamic Sciences Journal, 2026)
One of the most important tools that helps in understanding the Qur’anic text is the science called Qur’anic Sciences, which contains a number of sciences related to the Qur’an and its verses. This science arose with the revelation of the Qur’an, and then the classification and organization of it developed with the movement of authorship that was active during the Islamic Renaissance in its early ages. Contemporary scholars have made a clear contribution to the sciences of the Qur’an. Hence, we find that the writings of later scholars included many benefits and additions that cannot be denied in this science. Among the most important of the later scholars is Sheikh Fadl Abbas, may God have mercy on him, the author of useful writings, valuable observations, and unique investigations. His book, "Itqan al-Burhan fi Ulum al-Qur’an" (Mastering the Proof in the Sciences of the Qur’an), represents the pinnacle of scholarship in the sciences of the Holy Qur’an. This book is replete with numerous investigations and additions that have enriched the sciences of the Qur’an and its branches.